A March towards Reform: The Metaphorical Conceptualisation of ‘Reform’ in King Abdullah II’s Language - El-Sharif, Ahmad (Miscelánea: A Journal of English and American Studies, 2015)
Reform has recently become an imperative topic in Jordanian politics. After waiting long for tangible political and economic programs to be initiated by political parties, King Abdullah II of Jordan introduced his vision of reform. Reform is a priority, and this is plainly reflected in King Abdullah II’s “reformist” discourse. This paper adopts a critical linguistic approach to metaphor analysis to study King Abdullah II’s employment of metaphorical language to accentuate his authority, dominance, and ideologies in the implementation of a vision of reform. Qualitative and quantitative analysis of a corpus of King Abdullah II’s discourse demonstrates extensive use of metaphors from the conceptual domains of path, war (and conflicts) to conceptualise reform. It is found that the choice of such metaphors reflects King Abdullah II’s belief in implementing reform while maintaining a stable political and social system. This vision adopts a pragmatic and realistic position that is not deluding Jordanians or making them expect instantaneous positive outcomes from the reform process.